Family case of Schwachman-Diamond syndrome - M. G. Ipatova; N. A. Finogenova; Yu. G. Mukhina; P. V. Shumilov; A. I. Chubarova (Union of pediatricians of Russia, 2016)
Schwachman-Diamond syndrome is a disease characterized by exocrine pancreatic insufficiency, hematological disorders, growth retardation and bone abnormalities. The disease is caused by mutations in the SBDS gene. Early diagnosis and timely start of comprehensive treatment, including clinical nutrition, appointment of enzyme preparations and granulocyte colony stimulating factor, improve the quality of life and prognosis of these patients. The article describes the clinical observation of the Schwachman-Diamond syndrome's family case.